2020
DOI: 10.1097/qai.0000000000002384
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Existing Laboratory-Based Systems vs. Investing in Point-of-Care Assays for Early Infant Diagnosis of HIV: A Model-Based Cost-Effectiveness Analysis

Abstract: Background: To improve early infant HIV diagnosis (EID) programs, options include replacing laboratory-based tests with point-of-care (POC) assays or investing in strengthened systems for sample transport and result return. Setting: We used the CEPAC-Pediatric model to examine clinical benefits and costs of 3 EID strategies in Zimbabwe for infants 6 weeks of age. Methods: We examined (1) laboratory-based EID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Our total sample was relatively small; and we observed very few positive infants. Outcomes for HIV-positive infants-including timing of ART initiation and long term outcomes for HIV-positive infants-are an important aspect of evaluations for testing methods [31,32]. While very low yield of positive infants' results reflect the high coverage of antenatal ART and will likely continue to decrease, globally, as we strive towards elimination of mother-to-child transmission, it does prevent assessment of these critical impact data and forces us to rely on proxy measures such as timing of caregiver notification of results.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Our total sample was relatively small; and we observed very few positive infants. Outcomes for HIV-positive infants-including timing of ART initiation and long term outcomes for HIV-positive infants-are an important aspect of evaluations for testing methods [31,32]. While very low yield of positive infants' results reflect the high coverage of antenatal ART and will likely continue to decrease, globally, as we strive towards elimination of mother-to-child transmission, it does prevent assessment of these critical impact data and forces us to rely on proxy measures such as timing of caregiver notification of results.…”
Section: Plos Onementioning
confidence: 99%
“…POC diagnostic technologies such as GeneXpert HIV-1 Qual [ 15 ] and Alere m-PIMA [ 16 ] are cartridge-based tests that can be processed at the hospital by trained clinical or laboratory staff and can result in more rapid turnaround times of results, more infants being identified as HIV-positive and more infants initiated on ART at younger ages than traditional testing strategies [ 17 22 ]. Studies have shown high sensitivity and specificity of POC testing and found that POC implementation is feasible in hospital-based settings in Kenya [ 23 , 24 ], South Africa [ 18 , 25 27 ], Mozambique [ 28 ], and Tanzania [ 29 ]; is acceptable to providers [ 26 ] and patients [ 30 ]; and may be a cost-effective option for EID [ 31 , 32 ]. Based on the promising evidence supporting POC, the World Health Organization (WHO) conditionally recommended the introduction of POC for EID in 2016 [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unit costs per test are reported in Table 1. Seven studies reported unit costs for PoC assays [13,40,[50][51][52][53][54], 13 for laboratory testing [13,24,38,39,41,44,46,[50][51][52][53][54][55], two for rapid testing [41,56], and one for unspecified NAT [57] Variation in unit costs for PoC assays may be explained by inclusion of capital costs. Costs for m-PIMA that included equipment costs were > 20 USD higher than those that did not include equipment costs.…”
Section: Costs Per Hiv Early Infant Diagnosis Testmentioning
confidence: 99%
“…Few studies assessed the same intervention or reported costs in the same way, making comparison of costs across studies challenging. Most studies evaluated costs or cost-effectiveness of EID testing approaches including four studies on PoC EID [45,50,52,53], three on birth testing [24,44,59], one study that assessed both PoC and improvements to centralized EID [51], one that reported costs of confirmatory testing in EID programs [54], one of added screening of mothers at 6-week infant immunization visits with referral to EID for infants at risk of acquiring HIV [57], and one of rapid antibody screening to rule out negative infants before NAT [41].…”
Section: Hiv Early Infant Diagnosis Program Costsmentioning
confidence: 99%
See 1 more Smart Citation